A model-aided satellite-altimetry-based flood forecasting system for the Mekong River. (February 2019) - Chang, Chi-Hung; Lee, Hyongki; Hossain, Faisal; Basnayake, Senaka; Jayasinghe, Susantha; Chishtie, Farrukh; Saah, David; Yu, Hanwen; Sothea, Khem; Du Bui, Duong
Abstract: A freely accessible model-aided satellite altimeter-based daily water level forecasting system using simple regression analysis is proposed for the Mekong River with feasibility study being performed. In the Mekong Delta (MD), where Regional Flood Management and Mitigation Center (RFMMC) does not provide forecasting, ocean tides strongly impact river levels and were specifically addressed by the sum of 5-term sinusoidal function. Forecasting skills of our system are quite promising in the MD, although RFMMC's forecasting system has better skills than ours in the Mekong mainstem upstream of MD. In contrast to current operational system, our system circumvents the need of frequent altimeter samplings in the upstream by using the Variable Infiltration Capacity (VIC) macroscale hydrologic model with 0.1° resolution. The proposed forecasting system is computationally efficient without the need of complex hydrodynamic modeling, making such approach globally applicable for river basins and deltas with comparable forecasting skill and minimal computational cost. Highlights: Freely available daily river level forecasting in Mekong River is developed using satellite altimetry and VIC model. In Mekong Delta, mean absolute errors are <0.10 m, and efficiency coefficients are > 0.8 in 2011 - 2012 wet season. In Mekong Delta, up to 80% of days of 2011–2012 wet season has <0.15 m of absolute difference with in situ data.